Reducing food loss and waste contributes to energy, economic and environmental sustainability - Gage, Ewan; Wang, Xinfang; Xu, Bing; Foster, Alan; Evans, Judith; Terry, Leon A.; Falagán, Natalia (Elsevier, 2024)
Food loss and waste (FLW) reduction presents a major opportunity for enhancing the sustainability and resilience of the food supply chain. However, the lack of evidence regarding the scale and origins of FLW hinder determination of its environmental impact and prioritisation of mitigation action. We herein conducted a study to quantify FLW in the UK horticulture supply chain, and estimate its environmental impact as assessed through CO2 equivalent (CO2e) emissions. Through a metanalysis of existing literature supplemented with stakeholder engagement, we estimated that 2.4 Mt of fresh produce FLW is generated annually between farm gate and retail for home-grown and imported produce, representing 36% of total supply. FLW was perceived as an inevitable economic risk rather than a sustainability issue, driven by economic factors (e.g. labour shortage, price protectionism). The lack of economic incentives for FLW recovery (e.g. alternative processing) further compound FLW. Our results reveal that FLW contributes 1.7 Mt CO2e annually, constituting 27.2% of the total emissions of the fresh produce supply chain. Resource-intensive production, prolonged storage and complex handling needs generates substantial energy demand and concordant environmental impacts. The current over-reliance on cold chain management should be re-examined to disentangle the FLW-energy-environment nexus, especially given that the effects of global warming on the horticulture supply chain has yet to be examined. To effectively mitigate FLW, a holistic approach is imperative, encompassing policy and consumer-level changes alongside development of novel postharvest management strategies.
Keywords: Energy; Food policy; Postharvest; Logistics; Environmental impacts; Food loss and waste (FLW)